History and Its Limits Human, Animal, Violence - LaCapra, Dominick (Cornell University Press, 2010)
LaCapra regards this attempt to fix the difference as misguided and potentially dangerous because it renders insufficiently problematic the manner in which humans treat other animals and interact with the environment.In raising the issue of desirable transformations in modernity, History and Its Limits examines the legitimacy of normative limits necessary for life in common and explores the disconcerting role of transgressive initiatives beyond limits (including limits blocking the recognition that humans are themselves animals)